Analysis of the Role of Retribution for Building Permits on Regional Original Income at the Medan City Investment and One Stop Integrated Service Office - Tassa Al-Dawiyah; Sri Sudiarti (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the level of effectiveness of the role of Building Permit (IMB) levies on increasing Medan City Original Revenue 2018-2021. The research approach in this study is descriptive qualitative, namely conducting an in-depth study of the effectiveness of IMB Retribution Receipts based on facts. Primary data was taken through direct observation from observed sources and recorded for the first time at the Medan City Investment and One Stop Integrated Service Office. Secondary data are summarized from records and documents, as well as archives at the Medan City Investment and One Stop Integrated Service Office. The results of this study indicate that the effectiveness of the acceptance of the Medan City Building Permit Retribution (IMB) from 2018 to 2021 has increased every year. In 2018 the effectiveness of IMB receipts was 17.5%, and experienced a continuous increase until 2021 the effectiveness of IMB receipts was 130%. Meanwhile, the contribution of building construction permit levies (IMB) to local revenue (PAD) in Medan City is relatively small. So that the efforts made by the Medan City Investment and One-Stop Integrated Service Office need to be further improved.